Effect of Same-Temperature GaN Cap Layer on the InGaN/GaN Multiquantum Well of Green Light-Emitting Diode on Silicon Substrate. (4th December 2013) - Zheng, Changda; Wang, Li; Mo, Chunlan; Fang, Wenqing; Jiang, Fengyi
Abstract : GaN green LED was grown on Si (111) substrate by MOCVD. To enhance the quality of InGaN/GaN MQWs, same-temperature (ST) GaN protection layers with different thickness of 8 Å, 15 Å, and 30 Å were induced after the InGaN quantum wells (QWs) layer. Results show that a relative thicker cap layer is benefit to get InGaN QWs with higher In percent at fixed well temperature and obtain better QW/QB interface. As the cap thickness increases, the indium distribution becomes homogeneous as verified by fluorescence microscope (FLM). The interface of MQWs turns to be abrupt from XRD analysis. The intensity of photoluminescence (PL) spectrum is increased and the FWHM becomes narrow.